Analisis Pigmen Alami Daun Mangga (Mangifera Indicalinn) Sebagai Pewarna Batik Dengan UV-VIS - Ni Komang Tribuana Cipta Putri; I Gst Agung Ayu Ratnawati; Wayan Gede Suharta (Universitas Hamzanwadi, 2019)
The development of the batik industry has caused batik consumption to increase. Increased clothing and lifestyle needs trigger the need for practical (synthetic) dyes to have an impact on the waste produced. To reduce negative effects, the use of natural dyes needs to be increased. One of the plants that produce natural dyes is mango (Mangifera Indica Linn). Mango plants (Mangifera Indica Linn) including the family Anacardiaceae. The leaves contain a lot of chlorophyll which can produce color pigments for textiles. To find out the potential, an UV-VIS analysis was carried out, namely absorbance and calculation of the amount of chlorophyll contained in the leaves. The method used is the maceration process with technical ethanol solvents, with variations in concentration (70% and 96%) and variations in the immersion time (3 hours, 5 hours, 10 hours, 20 hours). From the results of UV-VIS spectrophotometry analysis showed the maximum absorption or absorbance at a concentration of 96% for 5 hours and the calculation of chlorophyll by the Lichtenthaler & Welburn (1983) method showed that the sweet arum manggu leaves used for research contained more chlorophyll b than chlorophyll a, gives a greenish-yellow pigment with wavelengths of 540 nm and 640 nm.